Importance de la norme linguistique dans l’autonarration des étudiants en philologie romane - Smuk, Maciej; Sujecka-Zając, Jolanta (Studia Romanica Posnaniensia, 2019)
The aim of this article is to analyse the attitude towards the linguistic norm of the first-year students of Romance Philology in Warsaw through the auto-narration. By this tool, belonging to the qualitative methodology, the learner performs a retrospective introspection and thus ‘evaluates’ the learning, in our context – his learning of grammar. The stories of students-future philologists will be analysed according to the following aspects: the importance given to the linguistic norm (understood here as the need for grammatical correction), the perception of its ‘utility’ in relation to other competences and language subsystems, the relationship between awareness of the norm and the effectiveness / quality of communication in a foreign language.